Pre-treatment quality of life as a predictor of distant metastasis-free survival and overall survival in patients with head and neck cancer who underwent free flap reconstruction. (August 2019) - Chen, M.N.; Ho, K.Y.; Hung, Y.N.; Su, C.C.; Kuan, C.H.; Tai, H.C.; Cheng, N.C.; Lin, C.C.
Abstract: Purpose: This study examined the prognostic associations of pre-treatment quality of life (QoL) with overall survival (OS) and distant metastasis-free survival (DFMS) among patients with head and neck cancer (HNC) who underwent free flap reconstruction. Methods: A cohort of 127 HNC patients who received free flap reconstruction between November 2010 and June 2014 at a hospital were recruited. Pre-treatment QoL was measured by the University of Washington Quality of Life Questionnaire, which contains six physical domains, including speech, swallowing, appearance, saliva, taste and chewing, as well as the six social-emotional domains of pain, activity, recreation, shoulder, mood, and anxiety. Cox regression analyses were performed. Results: Results showed that pre-treatment QoL was predictive of OS and DMFS. Of the domains, swallowing, chewing, speech, taste, saliva, pain and shoulder were demonstrated to be significant predictors of OS. Additionally, swallowing, chewing, speech, pain and activity were demonstrated making significant contributions to DMFS. Conclusion: Our data supported that physical domains of pre-treatment QoL were predictors for OS and DFMS in HNC patients with free-flap reconstruction. Longitudinal studies are warranted to clarify the prognostic abilities of social-emotional domains. Information on pre-treatment QoL should be taken into account to individualize care plan for these patients, and hence prolong their survival. Highlights: Some element of pre-treatment quality of life (QoL) was predictive of overall survival. Some element of pre-treatment QoL also predicted distant metastasis-free survival. Studies are needed to clarify the prognostic abilities of social-emotional domains. Information on pre-treatment QoL should be taken into account to design care plan.